An ecological assessment of the sustainable utilization of the woody vegetation in the Lowveld Bushveld, Mpumalanga Province - Van Rooyen, M.W. (Margaretha W.), 1950- (University of Pretoria, 2013)
Dissertation (MSc (Wildlife Management))--University of Pretoria, 2007.